Technology Adoption in a Decade: - Syahnur, Muh. Haerdiansyah; Rohman, Fatchur; Sumiati, Sumiati; Suryadi, Nanang (Journal of Accounting, Business and Management (JABM), 2025)
This study addresses the increasing complexity of understanding factors influencing technology adoption, particularly in developing countries where emerging technologies evolve rapidly. The research aims to identify and analyze dominant trends, theoretical frameworks, variables, and contextual factors shaping technology adoption over the past decade. Using a systematic literature review (SLR) of 57 Scopus-indexed articles published between 2015 and 2025, data were processed through the PRISMA protocol and analyzed using VOSviewer software and meta-synthesis techniques. The findings reveal that perceived ease of use and perceived usefulness remain the most prevalent determinants, while new psychological, social, and cultural dimensions—such as trust, autonomy, technophobia, and social influence—are gaining scholarly attention. Research from developing economies, notably India, Bangladesh, and Indonesia, highlights context-specific challenges and the transformative role of technology in digital ecosystems. The study contributes by proposing an integrative framework synthesizing TAM, TPB, UTAUT, and S-O-R models, offering a comprehensive foundation for future research, policymaking, and practical innovation in technology adoption.